The Use of Various Polymers with Solid Dispersion Application of Hot Melt Extrusion (HME) Preparing New Delivery Drug System - Sofi Nurmay Stiani (Journal of Global Pharma Technology, 2020)
Hot Melt Extrusion (HME) at the beginning appeared widely used in the plastic industry and food industry, but in the last few decades, many researchers have succeeded in applying the HME method as a drug delivery system and determining various dosage forms in the pharmaceutical industry. The challenges that arise in the pharmaceutical are related to the solubility, dissolution rate, and bioavailability of drugs, especially for drugs that have low solubility in water. The low solubility and bioavailability will reduce the pharmacological effect of a drug. Solid dispersion using HME method succeeded in answering this challenge by distributing the drug evenly in the hydrophilic polymer during the extrusion process and changing the crystalline form to the amorphous form while maintaining drug stability. This review will examine the polymers are suitable for the HME method, Mechanism for solid dispersion using HME method, Steps must be taken to prepare solid dispersions using HME and characterization of solid dispersion resulting from HME and determinants of success of solid dispersions Keywords: Polymer, Solid Dispersion, hot-melt extrusion, Mechanism of solid dispersion, Step HME.